Pengaruh Struktur Kepemilikan Saham, Profitabilitas, Dan Leverage Terhadap Pengungkapan Corporate Social Responsibility - Pramita, I Gusti Ayu Putu Inten Nanda; Ariyanto, Dodik (Jurnal Ilmiah Wahana Pendidikan, 2024)
The implementation of corporate social responsibility become a global trend, along with concern from people for the company’s social environment. The purpose of this study is to determine the effect of management ownership, foreign ownership, profitability, and leverage on corporate social responsibility disclosure during covid-19. This research was conducted on the IDX. The sampling method used purposive sampling. 17 property and real estate companies listed on IDX for 2020-2021 period were meet the research criteria with total 34 of observations. Data analysis technique were used multiple linear analysis. The result of this study showed management ownership, foreign ownership and profitability have no effect on Corporate Social Responsibility Disclosure. Leverage have significant effect on Corporate Social Responsibility Disclosure.